Sacred Wilderness - Power, Susan, 1961- (Book collections on Project MUSE., 2014)
A Clan Mother story for the twenty-first century, Sacred Wilderness explores the lives of four women of different eras and backgrounds who come together to restore foundation to a mixed-up, mixed-blood woman--a woman who had been living the American dream, and found it a great maw of emptiness. These Clan Mothers may be wisdom-keepers, but they are anything but stern and aloof--they are women of joy and grief, risking their hearts and sometimes their lives for those they love. The novel swirls through time, from present-day Minnesota to the Mohawk territory of the 1620s, to the ancient biblical world, brought to life by an indigenous woman who would come to be known as the Virgin Mary. The Clan Mothers reveal secrets, the insights of prophecy, and stories that are by turns comic, so painful they can break your heart, and perhaps even powerful enough to save the world. In lyrical, lushly imagined prose, Sacred Wilderness is a novel of unprecedented necessity.